Legal Study of Children with Emotional disturbance and Mental Health Needs and Implication for Practice - Dieterich, Cynthia A.; Snyder, Nicole D.; Villani, Christine J. (Journal of Law & Education, 2016)
Keywords: dept.cur; peer-reviewed

Online Research and Media Skills: An instructional model to support students as they search and shift online informational text - O'Byrne, W. Ian; McVerry, J. Gregory (Using Technology to Enhance Reading: Innovative Approaches to Literacy Instruction, 2015)
Enhance students' reading abilities with technology. Discover how technological resources can improve the effectiveness and breadth of reading instruction to build student knowledge. Read real-world accounts from literacy experts, and learn how their methods can be adapted for your classroom. Explore how to foster improvement in student learning using a variety of tools, including interactive whiteboards, tablets, and social media applications. Benefits:Gain insight into ways to incorporate technology into reading instruction.Obtain guidance on choosing progress-monitoring tools to best address your students' needs. Discover strategies to engage students in vocabulary instruction, and help students interpret informational texts. Learn how to use various tools to spark group discussions about literature. Determine how to continually assess students' connections with the assigned reading material. Contents: Part I: Reading Foundations Chapter 1: Foundational Reading Competencies Supported With Technology: Phonemic Awareness and Word Recognition Chapter 2: Rethinking Foundational Reading Skills: Making Room for the Complexities of Digital Texts Chapter 3: Using Tablets to Teach Foundational Skills: Matching Apps to Student NeedsPart II: Reading Fluency Chapter 4: Podcasts: Adding Power and New Possibilities to the Readers Theater Experience Chapter 5: Student-Produced Movies as Authentic Reading Fluency Instruction Chapter 6: Audio-Assisted Reading Builds Reading FluencyPart III: Reading Vocabulary Chapter 7: Post-Reading Vocabulary Development Through VSSPlus Chapter 8: Bringing Words to Life Through Student-Created Vocabulary Videos Chapter 9: Self-Regulated Vocabulary Learning on the InternetPart IV: Comprehension of Informational Texts Chapter 10: Using the Multimodal Explanatory Composition Strategy to Respond to Informational Texts Chapter 11: Annotation Apps: Supporting Middle School Students' Interpretation of Science Texts Chapter 12: Online Research and Media Skills: An Instructional Model for Online Informational TextsPart V: Comprehension of Literary Texts Chapter 13: Digging Deeper With Reader Response: Using Digital Tools to Support Comprehension of Literary Texts in Online Learning Environments Chapter 14: Coding and Connecting Complex Literature Chapter 15: Linking Through Literature: Exploring Complex Texts Through Hypertext Literary AnalysisPart VI: Reading Across Disciplines Chapter 16: Classroom Blogging to Develop Disciplinary Literacy Chapter 17: Using eReaders to Enhance Literacy Instruction in the Content Areas Chapter 18: Supporting Inquiry With Digital Texts in School DisciplinesPart VII: Motivation for Reading Chapter 19: "I Wanted to Film, So I Read the Book": Filmmaking in the English Classroom Chapter 20: eBooks and eReaders: Removing Obstacles, Improving Motivation Chapter 21: Using Literacy iPad Apps for Reading MotivationPart VIII: Reading Assessment Chapter 22: Literacy Assessments in the Digital Age Chapter 23: Developing and Assessing Fluency Through Web 2.0 Digital Tools Chapter 24: Using Blogs as Formative Assessment of Reading Comprehension
Keywords: dept.cur

Implicit Attitudes of International and American Adult Students toward Black and White Teachers - Na, Eunkyung; Tan, Tony X.; Marn, Travis; Ramirez, Rica (Commission for International Adult Education, 2015)
The purpose of this study was to examine hidden prejudice in two groups of adult students, international and American, against black compared to white teachers. Social desirability in the minds of participants may affect the result of a study involving racial bias (Mullins, 1982). For this reason, the researchers created a computer protocol using the standard Implicit Association Test (IAT) to measure the implicit attitudes of participants. The IAT relies on the idea of automatic information process within the mind that is not impacted by social desirability. A clear concern in education is that the racial bias toward minority students will let those implicit biases affect the way they teach those students, creating a self-fulfilling prophesy of poor student performance. But the implicit bias can work both ways and can impact a teacher's effectiveness. Traditional racial prejudice theories usually looked at white's attitudes toward blacks and other groups. This study had a significant directional shift by focusing on the international students' racial attitudes toward black and white teachers. The implicit racial attitudes of international students were also compared to those of American students. The result and evaluation of this study may be a valuable tool to improve student services and teacher professional development in higher education. Suggestions for future research are also provided.[For full proceedings, see ED570489.]
Keywords: Adult Students; African American Teachers; Attitude Measures; College Students; Comparative Analysis; Foreign Students; Gender Differences; Racial Attitudes; Racial Bias; Social Desirability; Statistical Analysis; Student Attitudes; Surveys; Whites; dept.cur

Biracial Place Walkers on Campus: A Trioethnography of Culture, Climate, and Currere - Agosto, Vonzell; Marn, Travis; Ramirez, Rica (International Review of Qualitative Research, 2015)
Send this e-mail to Rica and Travis: Rica and Travis, I wish you could have been at the duoethnography panel. The first presentation had some uneasy conversations. The second, Dr. Colomer's presentation, was cool: A performance with guest actors had some sad moments with death, health issues, and attrition. The next presentation was about miscarriage and grief counseling. I wondered if our paper is frivolous in comparison to the others. I think not. Our episodes of cultural starvation and indifference are there and painful, but our comebacks are so quick (nourishment as resistance), and therefore so is the celebration. Written by Agosto while flying home after presenting at the 2014 International Congress of Qualitative Inquiry.
Keywords: dept.cur

Adoptive Parents’ Suspicion and Coping With the Possibility of Child Abduction for International Adoption in China - Marn, Travis M.; Tan, Tony Xing (The Family Journal, 2015)
In this study, we investigated (1) whether adoptive parents suspected their children might have been victims of abduction for adoption in China and (2) for parents who were uncertain if their own children might be victims of child abduction for adoption, how they coped with the possibility. A total of 342 adoptive parents (representing 529 adopted Chinese children) completed an anonymous online survey on their experiences. Of the 342 parents, 154 (45%) described how they coped with the possibility that their children might be the victims of child abduction for adoption. In terms of suspicion, we found that for about 70% of the children, the parents responded Never; for 18.5% of the children, the parents responded Rarely; for 11.7% of the children, the parents responded Sometimes; and for about 1% of the children, the parents responded that they Always suspected that their children might be victims of abduction for adoption. In terms of coping with the possibility that their children might have been victims of child abduction for adoption, thematic analysis on the 154 parents’ descriptions revealed that parents experienced one or more of seven emotional reactions: sadness, frustration/helplessness, complicity/guilt, anger, fear/worry, hypervigilance, resolve, as well as the belief that they were not affected. Finally, we discussed contributing factors to child abduction for adoption and to adoptive parents’ suspicion of such a practice.
Keywords: dept.cur

Purposeful Entanglements: A New Materialist Analysis of Transformative Interviews - Marn, Travis M.; Wolgemuth, Jennifer R. (Qualitative Inquiry, 2017)
In this article, we explore transformative interviewing through the lens of new materialism. Rather than viewing transformation through a humanist perspective that centralizes a transcendent self, we draw upon Barad’s agential realism to reconsider transformation following the ontological turn. Thinking with agential realism, we engaged two interview studies, one on biracialism and one on masculinity, to demonstrate how the materiality of our interviews (e.g., research bodies, computer programs, questionnaires) intra-acted with our participants to both facilitate and hinder our attempts at transformation. We conclude by theorizing transformation as a type of purposeful entanglement that proceeds from the material-discursive intra-actions of our inquiries.
Keywords: dept.cur

Work/Think/Play/Birth/Death/Terror/Qualitative/Research - Wolgemuth, Jennifer R.; Rautio, Pauliina; Koro-Ljungberg, Mirka; Marn, Travis M.; Nordstrom, Susan; Clark, Adam (Qualitative Inquiry, 2018)
Inspired by work/think/play in qualitative research, we centered the idea of “play” in a qualitative research project to explore what proceeding from the idea of work/think/play might look like and accomplish. We pursued play in an experimental qualitative inquiry over dinner one night at the 2016 Annual Meeting of the American Educational Research Association. Our article centers on one work/think/play inquiry three of us conducted. Through a playful account of how play unfolded in our work/think/play inquiry that evening, we explore research play as generative, deadly, and censored in the context of neoliberalism and other terrors. We reflect on what (good) play does in qualitative research, what our work/think/play/birth/death/terror/qualitative/research accomplished, if anything. Maybe research play is vital, what keeps us fit to do critical qualitative research. Yet research play moves (well) beyond normative rules of much qualitative research. Is it worth the risk? Can we know? Even after?
Keywords: dept.cur

Creating a Space for Teacher Candidates Committeed to Urban Settings: Action Research Program on the Urban Education Fellows Program - Bower-Phipps, Laura; Marx, H. A. (Teacher Education Yearbook XXIV: Establishing a Sense of Place for All Learners in 21st Century Classrooms and Schools, 2015)
The Association of Teacher Educators (ATE) Yearbook XXIV offers 16 captivating chapters related to establishing a sense of place or belonging for P-12 students, classroom teachers, teacher candidates, and teacher educators. The chapters include theory, research, concepts, principles, practices, and programs that inform and support as well as question and challenge readers from multiple perspectives. Readers gain insights and inspiration that illustrate ways teachers and learners negotiate meaning in environments where everyone experiences social and cultural connections with personal and academic fulfillment. Collectively, the authors identify, describe, analyze, and advance issues associated with creating both an individual and a shared sense of place among the ever-changing populations in contemporary P-12 schools and classrooms. Like human geographers, teacher educators and educational researchers study environments where children grow up and create bonds with their early environments that continue to influence them throughout their lives based on the ways in which meaning is negotiated in that early space. Candidates, teachers, and teacher educators benefit by investigating the presence and power of these landscapes impacting the teaching, learning, and schooling.
Keywords: Education / Administration / General; Education / Educational Policy & Reform / General; Education / Inclusive Education; Education / Learning Styles; Education / Student Life & Student Affairs; dept.cur

Developing as Teachers and as Researchers: Emerging Professionals' Experiences with Cooperative Inquiry - Bower-Phipps, Laura; Cruz, Maria; Albaladejo, Cristina; Johnson, Arlette; Homa, Thomas (Networks: An Online Journal for Teacher Research, 2016)
This article details the second cycle of cooperative inquiry undertaken by emerging educators who self-identify as "other" because of gender, language, ethnicity, and/or sexual orientation. The current cycle focuses on the impact participation in cooperative inquiry had on researchers' teaching practices. Data sources include transcripts of group discussions and reflective writing completed six months, eighteen months, and two years after the completion of the first cycle of cooperative inquiry. Findings suggest that as a result of engagement in cooperative inquiry, the teacher/researchers established practices to decrease isolation, build unity, and understand students' backgrounds. Teacher/researchers viewed themselves as advocates for diversity within the classroom, took a collaborative approach to teaching, and came to see research as an essential element of effective teaching.
Keywords: Beginning Teachers; Cooperation; Educational Practices; Elementary School Teachers; Inquiry; Minority Group Teachers; Preservice Teachers; Self Concept; Social Distance; Student Teachers; Teacher Educators; Teacher Researchers; dept.cur

New Literacies of Online Reading Comprehension - Leu, Donald J.; Everett-Cacopardo, Heidi; Zawilinski, Lisa; McVerry, Greg; O'Byrne, W. Ian (The Encyclopedia of Applied Linguistics, 2012)
Literacy has become deictic (Leu, 2000); the meaning of literacy is rapidly changing as new technologies for literacy continually appear and new social practices of literacy quickly emerge.
Keywords: Internet; dept.cur; language in the classroom; literacy; online reading comprehension; reading

The personal is professional: Unpacking cultural sanctions through the identities of mother /educator/lesbians - Bower-Phipps, Laura (Sexual Orientation and Teacher Identity: Professionalism and LGBTQ Politics in Teacher Preparation and Practice, 2019)
Keywords: dept.cur; dept.eng

Developing mentors: an analysis of shared mentoring practices - Bower-Phipps, Laura; Klecka, Cari Van Senus; Sature, Amanda L (The New Educator, 2016)
Understanding how experienced teachers share and articulate effective mentoring practices can guide efforts to prepare quality mentors. This qualitative study focused on mentoring practices within a teacher-designed student-teaching program conceptualized while the mentor teachers within the program were students in a graduate-level mentoring course and implemented upon the mentors’ completion of their graduate studies. Data sources included interviews and field notes from meetings with mentors and student teachers. The results detail specific mentoring practices: explicit instruction through scaffolding, developing the whole teacher, student-teacher-directed learning, fostering student teachers’ individual practice, explicit mentoring of one another, and reflecting on mentoring. These practices were enabled by program structures such as mentor meetings, an online forum, and mentors’ observation of all student teachers in the program. © 2016, © 2016 CCNY and ATE.
Keywords: dept.cur; peer-reviewed

Valuing stuff materials culture and artifactual literacies in the classroom - Randall, Regine; Mercurio, Mia Lynn (Journal of Adolescent & Adult Literacy, 2015)
Recent interest in materials culture and artifactual literacies has helped the authors of this article rethink how they teach preservice and inservice teachers and collaborate with K-12 teachers. Each discipline has its own stuff that can help students understand the products and practices of a field beyond what they might be able to glean from text. To that end, every teacher should see their classroom and content area as a "place for my stuff" because objects speak and communicate more messages through form, color, size, and texture than print alone. © 2015 International Literacy Association.
Keywords: 3-Early adolescence; 4-Adolescence; 5-College/university students; Adolescent/young adult literature; Content analyses; Content literacy; Discussion strategies; Information literacy; Informational text; Instructional strategies; Literary elements; Specific subject areas (math; Strategies; Text types; and materials; art; dept.cur; dept.sed; etc.); methods; teaching strategies; text features

Guiding students as they explore, build, and connect online - McVerry, J. Gregory; Belshaw, Doug; O'Byrne, W. Ian (Journal of Adolescent & Adult Literacy, 2015)
Keywords: dept.cur

Improving students' academic learning by helping them access text - Ben-Avie, Michael; Randall, Régine; Dunne, Diane Weaver; Kelly, Chris (Recent Advances in Assistive Technologies to Support Children with Developmental Disorders, 2015)
Conventional methods of addressing the needs of students with print disabilities include text-to-speech services. One major drawback of text-to-speech technologies is that computerized speech simply articulates the same words in a text whereas human voice can convey emotions such as excitement, sadness, fear, or joy. Audiobooks have human narration, but are designed for entertainment and not for teaching word identification, fluency, vocabulary, and comprehension to students. This chapter focuses on the 3-year pilot of CRISKids; all CRIS recordings feature human narration. The pilot demonstrated that students who feel competent in their reading and class work tend to be more engaged in classroom routines, spend more time on task and demonstrate greater comprehension of written materials. When more demonstrate these behaviors and skills, teachers are better able to provide meaningful instruction, since less time is spent on issues of classroom management and redirection. Thus, CRISKids impacts not only the students with print disabilities, but all of the students in the classroom.
Keywords: dept.cur

Multimodal response and writing as poetry experience - Pet, Sue Ringler; Mcverry, J Gregory; Obyrne, W Ian (Exploring Multimodal Composition and Digital Writing, 2014)
What affordances do multimodal and digital information provide to the student and teacher with regard to responding to and writing poetry? This question juxtaposes one of the oldest literary genres in human history (i.e., poetry), with some of the newest technologies available. To enrich the content and effect as students experience poetry, technology may seem like an unwelcome stranger. Research has found, however, that “multimedia texts and multimodal composing may actually shift classroom culture toward a more learner-centered paradigm” (Chandler-Olcott & Mahar, 2003, pp. 381-382). This chapter explores the integration of technology with both response to poetry and authorship of poetic works as a means to enrich English classroom experiences. In the authors’ view, important work in this arena must not use technological tools for the sake of using technology in the classroom, but, rather, for the sake of enriching literary experiences. Ultimately, by connecting response, authorship, and multimodal technologies, the teaching of poetry may be enhanced by the teaching of 21st century literacy skills. Toward these ends, the authors share opportunities for intertwining multimodal text with the teaching of poetry to enrich literacy and literary experience in middle and high school classrooms.
Keywords: dept.cur

Vowel representations in the invented spellings of Spanish-English bilingual kindergartners - Raynolds, Laura B.; Uhry, Joanna K.; Brunner, Jessica (Reading and Writing, 2013)
The study compared the invented spelling of vowels in kindergarten native Spanish speaking children with that of English monolinguals. It examined whether, after receiving phonics instruction for short vowels, the spelling of native Spanish-speaking kindergartners would contain phonological errors that were influenced by their first language. Results showed no differences between the two groups on the number of correct short vowel spellings, even though the sounds for four of the five English short vowels do not exist in Spanish. By contrast, differences were observed in the representation of long vowels with a higher rate of error among ELLs. The students had not received explicit instruction in long vowels. ELLs appeared to be trying to represent the diphthongized nature of some English long vowels by spelling long vowels with more than one vowel. The results support the authors' hypothesis that kindergarten phonics instruction had an impact on the invented spellings of new second language vowel phonemes.
Keywords: Bilingual; English language instruction; Invented spelling; Spanish language; dept.cur; peer-reviewed

Everyone has a story: A collaborative inquiry project by five teacher candidates of color and one white professor - Bower-Phipps, Laura; Tate, Rachel Watanabe; Mehta, Sejal; Sature, Amanda L (Current Issues in Education, 2013)
Initiatives to increase the number of teachers of color in U.S. public schools must be accompanied by culturally relevant teacher preparation for candidates of color. This study is a cooperative inquiry (Heron, 1996) conceived, conducted, and analyzed by five preservice teachers of color and one of their professors, a white lesbian. The women met biweekly for a year to co-construct meaning from their experiences in a teacher education program. They analyzed data sources together, including meeting transcripts, autobiographical sketches, and reflective writing on themes from the data. Key findings include the complexity of teacher candidates' identities; the importance of support systems for teacher candidates of color, particularly within predominantly white contexts; the connection between teacher candidates' backgrounds and their visions as teachers; and the role others' perceptions, particularly teacher educators, have played in teacher candidates becoming teachers.
Keywords: Cooperative inquiry; Diversity; Teacher identity; Teachers of color; dept.cur; peer-reviewed; ⛔ No DOI found

The new literacies of online reading comprehension: expanding the literacy and learning curriculum - Leu, Donald J.; McVerry, J. Gregory; O'Byrne, W. Ian; Kiili, Carita; Zawilinski, Lisa; Everett-Cacopardo, Heidi; Kennedy, Clint; Forzani, Elena (Journal of Adolescent & Adult Literacy, 2011)
Keywords: dept.cur

Surpassing normal: preparing teachers for diverse learners - Bower, Laura A; Sature, Amanda L (Action in teacher education, 2011)
Teacher education must prepare teacher candidates for diverse contexts and diverse learners. Such preparation involves teacher candidates unearthing their assumptions about diverse populations and understanding the roles candidates' own backgrounds play in these assumptions. Queer theory can facilitate this process through attention to culturally constructed notions of “normal” and “deviant.” This chapter investigates a strategy intended to identify teachers' cultural expectations through disrupting candidates' perceptions of “normal” students. Data sources include responses to a specific learning activity, interviews, and demographic surveys. Findings indicate that teacher candidates are reluctant to discuss certain demographic descriptors, such as race/ethnicity and sexual orientation, preferring to focus on students' interests and social behaviors. candidates' conceptions of a “normal” student mirror their own experiences. Interview responses suggest that the learning activity disrupted these conceptions. Implications point to the importance of discussing diversity in teacher education courses and the necessity of fieldwork in diverse contexts. © 2011, Copyright Association of Teacher Educators.
Keywords: dept.cur

Braiding teacher practice and class-wide dialogue: An historical inquiry across three sociocultural interventions - Palincsar, Annemarie Sullivan; Marcum, Meredith Baker; Fitzgerald, Miranda; Sherwood, Carrie-Anne (International Journal of Educational Research, 2019)
Keywords: dept.cur; peer-reviewed

Start here, or here, no here: introductions to rethinking education policy and methodology in a post-truth era - Wolgemuth, Jennifer R.; Koro-Ljungberg, Mirka; Marn, Travis M.; Onwuegbuzie, Anthony J.; Dougherty, Shaun M. (Education Policy Analysis Archives, 2018)
This special issue takes up urgent questions about how we education scholars might think and do policy and methodology in what has come to be known as the post-truth era. The authors in this special issue grapple with questions about the roles and responsibilities of educational researchers in an era in which research and policy have lost their moorings in T/truth. Collectively they reconceptualize educational research and policy in light of post-truths, anti-science sentiment, and the global rise of right-wing populism. At the same time we editors wonder whether post-truth is given a bad rap. Could post-truth have something productive to offer? What does post-truth open up for educational research and policy? Or, is the real issue of this special issue a collective despair of our own insignificance and obsolescence in the wake of post-truth. Whatever we editors and authors aimed to do, this special issue will not be heard by post-truth adherents and partisans. Perhaps its only contribution is encouragement to stay with the troubles of a post-truth era, even as we despair the consequences of our research and policy creations. © 2018, Arizona State University. All rights reserved.
Keywords: Education policy; Fake news; Methodology; Post-truth; dept.cur; peer-reviewed

Examining the work of “scaffolding” in theory and practice: A case study of 6th graders and their teacher interacting with one another, an ambitious science curriculum, and mobile devices - Palincsar, Annemarie Sullivan; Fitzgerald, Miranda Suzanne; Marcum, Meredith Baker; Sherwood, Carrie-Anne (International Journal of Educational Research, 2018)
This case study features a class of sixth-grade students and their science teacher enacting a curriculum designed to teach the particulate nature of matter and phase changes. The class used a mobile device with several applications that supported reading, writing, viewing, and modeling. We examine the role of the teacher, the device, the peers, and the curriculum itself in scaffolding student learning.
Keywords: Collaboration; Conceptual understanding; Modeling; Peer-mediated learning; Scaffolding; States of matter; Zones of proximal development; dept.cur; peer-reviewed

Joyfully engaged in multimodal learning - Shaw, Louise J. (Promoting social emotional learning in the classroom: Creativity, connections, and engagement, 2017)
Keywords: dept.cur

It’s all Greek: Ancient history as a community journey - Shaw, Louise J. (Impacting literacy through home and community connections, 2017)
Keywords: dept.cur

Teaching students to write: Arguing against the overuse of argument - Randall, Régine; Mercurio, Mia Lynn (Kappa Delta Pi Record, 2017)
This personal editorial written by two education professors considers the Common Core State Standards and argues against the overuse of argument in the teaching of writing. © Kappa Delta Pi.
Keywords: Common core; Writing; dept.cur; dept.sed

Exploring English and Spanish rhyme awareness and beginning sound segmentation skills in prekindergarten Spanish-speaking English Learners - Raynolds, Laura B.; López-Velásquez, Angela; Olivo Valentín, Laura E. (Reading and Writing, 2017)
Twenty-five 4- and 5-year-old Spanish-speaking English Learners (ELs) were tested in order to compare their English and Spanish performance in two phonological awareness skills: Rhyme awareness (RA) and beginning sound segmentation (BSS). The children had received formal instruction of phonological awareness, with an emphasis on RA and BSS for 1 year and in English only, using the Opening the World of Learning curriculum (Schickedanz & Dickinson, 2005). The results showed that the children scored higher on the English BSS than on the English RA tests (p ¡ .001), even though RA is generally considered to be an earlier developing skill than BSS among English-monolingual children. No significant difference was found between the English BSS and Spanish BSS tests despite the fact that the children had received English-only instruction in these phonological awareness skills for 1 year. The results are discussed in terms of the possible impact of the similarities and differences between the Spanish and English linguistic structures on the learning and cross-linguistic transfer of phonological awareness skills in young Spanish-speaking ELs.
Keywords: Beginning sound segmentation; English-only instruction; Phonological awareness; Prekindergarten; Rhyme awareness; Spanish-speaking English Learners; dept.cur; dept.sed; peer-reviewed